Participatory Management perceptions and Opinions of Forest Dependent Communities in Tanzania - Lokina Razack; University of Dar es Salaam (Dar es Salaam Dar es Salaam University Press, 2011)
This study was initiated to provide current information about people?s perceptions and opinions about the implemented Participatory forest management (PFM) programmes in Tanzania. It also sought to find out the factors that influence households? perceptions about the successfulness of PFM programmes. Data for this study was obtained from a random sample of 1023 households in Morogoro and Tanga districts. Descriptive results show that households perceive the PFM initiatives as being successful with a positive impact to the community but also felt that they are not given enough opportunity to participate in decision making. The Multinomial Logit regression results show that household?s perceptions on the success of the PFM programme are influenced by spatial characteristics, livestock ownership and dependence on fuelwood. The findings in this paper can be used by government and other stakeholders to improve on the way they deliberate on PFM issues and to address appropriate forest management practices.
Keywords: Perceptions and Opinions